Improved method for calculation of parameters of electromagnetic and power processes in electric circuits with steel in saturation mode - Zagirnyak, M.; Prus, V.; Miljavec, D. (Технічна електродинаміка, 2015)
The reasons for increased degree of saturation of magnetic system of electric machines with a long error-free running
time are substantiated. It is proved that application of the conventional methods of calculation of electromagnetic and
power processes parameters at practical degrees of saturation results in inadmissible errors. During the process of the
problem solution an improved parameter calculation method applicable under the considered conditions is grounded. A
sufficient degree of coincidence of the calculation results with the experimental data as to integral parameters and instantaneous
power and electromagnetic characteristics is obtained. Обґрунтованo причини підвищення ступеню насичення магнітної системи електричних машин із тривалим наробітком
на відмову. Доведено, що застосування існуючих методів розрахунків параметрів електромагнітних та енергетичних
процесів при ступенях насичення, що зустрічаються на практиці, приводить до неприпустимих похибок.
У процесі розв'язку задачі обґрунтовано уточнений метод розрахунку параметрів, застосовний у розглянутих умовах.
Отриманий достатній ступінь збігу результатів розрахунків з даними експериментів за інтегральними параметрами
та миттєвими енергетичними й електромагнітними характеристиками. Обоснованы причины повышения степени насыщения магнитной системы электрических машин с продолжительной
наработкой на отказ. Доказано, что применение существующих методов расчета параметров электромагнитных
и энергетических процессов при встречающихся на практике степенях насыщения приводит к
недопустимым погрешностям. В процессе решения задачи обоснован уточненный метод расчета параметров,
применимый в рассматриваемых условиях. Получена достаточная степень совпадения результатов расчетов
с данными экспериментов по интегральным параметрам и мгновенным энергетическим и электромагнитным
характеристикам.